Heteropolymetallic aggregates from [Pd2(dppf)2(μ-S)2]. Bonding and structural analysis of [Ag2Pd2Cl2(dppf)2(μ 3-S)2]·4CH2Cl2 [dppf = Fe(C5H4PPh2)2] - A flat Pd2S2 core with two AgCl 'tails' - Li, G. (2014)
Journal of the Chemical Society - Dalton Transactions